Exploring ceRNA mechanisms in COVID-19 mRNA vaccine-induced myocarditis: implications for future vaccine design - Wang, Jing; Sun, Xin-Yi; Gao, Qian; Fu, Min; Xiao, Mian; Du, Ning; Ge, Xi-Yuan (Frontiers in Immunology, 2025)
IntroductionThe emergence of Coronavirus Disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) necessitated the rapid development of effective vaccines, with mRNA vaccines demonstrating high efficacy and accelerated production timelines. However, reports of myocarditis following mRNA vaccination have raised safety concerns, and the underlying molecular mechanisms remain poorly understood.MethodsHuman AC16 cardiomyocytes were transfected with in vitro transcribed (IVT) COVID-19 mRNA modified with N1-methylpseudouridine (m1Ψ). A panel of inflammatory cytokines, including IL-6, was quantified using a Luminex liquid suspension chip. IL-6 expression was further validated at the mRNA level by RT-qPCR and at the protein level by ELISA. Cardiomyocyte apoptosis was assessed by flow cytometry. Myocardial injury biomarkers, specifically Creatine Kinase-MB (CK-MB) and cardiac troponin I (c-TnI) were measured by ELISA. The ceRNA interaction was investigated through RNA immunoprecipitation (RIP), and dual-luciferase reporter assays.ResultsIVT mRNA elicited a robust inflammatory response in cardiomyocytes, markedly upregulating the proinflammatory cytokine IL-6 (~2-fold). Under inflammatory conditions, IVT mRNA further exacerbated IL-6 secretion (~2-fold) and increased cardiomyocyte apoptosis (~1.3-fold). Additionally, IVT mRNA significantly elevated the levels of CK-MB (~1.5-fold) and c-TnI (~2-fold). Mechanistically, IVT mRNA functions as a competing endogenous RNA (ceRNA) for hsa-let-7f-5p, alleviating its suppression of IL-6 mRNA, and enhancing inflammatory responses in AC16 cardiomyocytes.DiscussionThis study elucidated a molecular mechanism linking COVID-19 mRNA vaccines to myocarditis and highlighted the ceRNA-mediated crosstalk between IVT mRNA and IL-6. These findings underscore the importance of avoiding critical microRNA binding sites in the design of next-generation mRNA vaccine sequences to improve safety.